Characterization of inflammation in a rat model of acute lung injury after repeated pulmonary lavage. (14th September 2015) - Menk, Mario; Graw, Jan Adriaan; Steinkraus, Henrik; Haefen, Clarissa von; Sifringer, Marco; Spies, Claudia D.; Lachmann, Burkhard; Schwaiberger, David
ABSTRACT: Aim of the study: Repeated pulmonary lavage allows to reliably reproduce failure of gas exchange and major histological findings of acute lung injury (ALI). However, because the capacity of pulmonary lavage to induce pulmonary inflammation is not well established in rodents, this study aims to characterize the induction of pulmonary inflammation in a rat model of ALI. Materials and Methods: Male adult rats were divided into a treatment group ( n = 9) that received pulmonary lavage with consecutive mechanical ventilation, and a control group that received mechanical ventilation only ( n = 9). Arterial blood gas analyses were performed every 30 min throughout the study. Pressure-volume curves, and lung tissue and plasma samples, were obtained at 240 min after the start of mechanical ventilation. Protein content and surface activity of bronchoalveolar lavage fluid was assessed. Transcriptional and translational regulation of pro- and anti-inflammatory cytokines IL-1β, TNF-α, IL-6, and IL-10 was determined in lungs and plasma. Markers of cellular stress were measured in lung tissue. Results : Pulmonary lavage significantly decreased lung compliance, induced hypoxia and hypercapnia, and mediated respiratory acidosis. Protein content of lavage fluid was significantly increased and contained washed out surfactant. Expression of IL-1β, TNF-α, and IL-6 mRNA and protein expression of IL-1β and TNF-α was significantly induced in lavaged lungs, without spillover into the systemic circulation. Markers of cellular stress were significantly upregulated in lavaged lungs. Conclusions : This model of ALI applied in rats can induce pulmonary inflammation. The model might be used to develop therapeutic strategies that target pulmonary inflammation in ALI.